Thermofluid patterns at liquid surface with non-uniform heating - Lim, Kenneth Zhi Hui (Nanyang Technological University, 2021)
Hydrothermal wave patterns are a natural occurrence when sessile liquid droplets evaporate. These patterns are affected by many different variables and they are widely studied as the results and observations can be used to improve technologies that are used in many different industries. Under the assistance of infrared cameras these patterns are revealed, and their behaviour will be studied over the droplet evaporation lifetime. In the present study, thermal patterns will be investigated under non-uniform heating as the temperature and temperature gradient within the droplet starts to vary. Pure ethanol droplets were chosen to be the working fluid for this study. 20µL of pure ethanol will be ejected onto a copper substrate and put through non-uniform heating hence inducing a temperature gradient within the water droplet. It was observed in the experiment when the temperature gradient equals to zero, the thermal wave patterns are found to be uniform and equal in size. As the temperature gradient starts to increase, the thermal wave pattern becomes non-uniform. Another phenomenon that was observed was that as the temperature increases the total number of visible waves increases with the temperature. At 30°C there was 18 visible waves as the temperature increases to 45°C there was 31 waves and at 60°C 36 waves. Future study relating to this topic can consider acquiring better and more precise heating-cooling machine to achieve a wider temperature gradient. With a wider temperature gradient, more patterns and different observation could be uncovered and be studied in-depth.